2021
DOI: 10.1097/dbp.0000000000000996
|View full text |Cite
|
Sign up to set email alerts
|

Racial, Ethnic, and Sociodemographic Disparities in Diagnosis of Children with Autism Spectrum Disorder

Abstract: : This special article uses a biosocial-ecological framework to discuss findings in the literature on racial, ethnic, and sociodemographic diagnostic disparities in autism spectrum disorder. We draw explanations from this framework on the complex and cumulative influences of social injustices across interpersonal and systemic levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(49 citation statements)
references
References 69 publications
3
37
0
Order By: Relevance
“…2) low awareness of developmental disabilities (Whittle et al, 2018); 3) distrust of healthcare professionals (Zeleke et al, 2019); 4) fear of not being believed (Lewis, 2017); 5) misgendering or sex bias in characterizing disability conditions (Bargiela et al, 2016;Santos et al, 2022); and 6) low cultural competency in patient-provider interactions (Aylward et al, 2021;Eken et al, 2021). Some still cannot access a formal diagnosis when missed as a child due to living in a LMIC or region, immigration status, lack of healthcare coverage, language/communication barrier, or lack of access to a professional licensed to conduct diagnostic evaluations.…”
Section: Intersection Of Neurodivergence and Socioeconomic Statusmentioning
confidence: 99%
“…2) low awareness of developmental disabilities (Whittle et al, 2018); 3) distrust of healthcare professionals (Zeleke et al, 2019); 4) fear of not being believed (Lewis, 2017); 5) misgendering or sex bias in characterizing disability conditions (Bargiela et al, 2016;Santos et al, 2022); and 6) low cultural competency in patient-provider interactions (Aylward et al, 2021;Eken et al, 2021). Some still cannot access a formal diagnosis when missed as a child due to living in a LMIC or region, immigration status, lack of healthcare coverage, language/communication barrier, or lack of access to a professional licensed to conduct diagnostic evaluations.…”
Section: Intersection Of Neurodivergence and Socioeconomic Statusmentioning
confidence: 99%
“…The more widespread use of these culturally responsive practices among educational professionals may be helping to reduce racial/ethnic disparities in receipt of special education for students with ASD. Beyond the educational setting, it is also worth noting that many children from minoritized backgrounds are not able to access timely diagnoses from healthcare providers (Aylward et al, 2021). As the current sample was limited only to children who had been diagnosed with ASD by a healthcare professional, the extent to which these persistent health care disparities lead to educational inequities cannot be fully examined.…”
Section: Discussionmentioning
confidence: 99%
“…1 Research has reported racial and ethnic disparities, with White children diagnosed earlier and more often than children in other racial and ethnic groups, 2 and negative outcomes resulting from these disparities. 3 A 2019 report from the Centers for Disease Control and Prevention (CDC) suggests these gaps are closing. 4 This cohort study assesses racial and ethnic parity across rates and age at ASD diagnosis.…”
Section: Introductionmentioning
confidence: 99%